2015
DOI: 10.1155/2015/953164
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Drying Methods on Constituents and Antioxidant Activity of Saffron from China

Abstract: More and more saffron has been cultivated in China because of the increasing saffron demand, but no paper has studied the influence of drying methods on the quality of Chinese saffron. In this paper, three different dehydration treatments applied in actual production were evaluated: dehydration with electric oven, vacuum oven, and microwave. We determined that the highest quality of saffron will be obtained when fresh saffron is treated at higher temperatures (no more than 70°C) for a long time by electric ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Tong et al concluded that drying treatment at lower microwave power and over a longer time benefitted the quality of saffron. In this work, the authors suggested that the highest quality of saffron is obtained when fresh saffron is dried at a high temperature, no more than 70 °C, using an electric or vacuum oven [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tong et al concluded that drying treatment at lower microwave power and over a longer time benefitted the quality of saffron. In this work, the authors suggested that the highest quality of saffron is obtained when fresh saffron is dried at a high temperature, no more than 70 °C, using an electric or vacuum oven [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, saffron in Spain is obtained by C. sativus L. stigmas dried by a process called “toasting”, in which stigmas are put on a sieve with a silk bottom placed over a heating source, whereas in other countries, in terms of temperature, stigmas are dehydrated at room temperature under sunlight or in the shade. Stigmas’ dehydration is the key process to obtaining the spice and is responsible for saffron composition [ 4 , 5 , 6 ]. During this process, stigmas lose around 80% of their weight and, according to the International Standard ISO 3632 (2011) [ 7 ], moisture must be lower than 12% in order to preserve the spice for a long time [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quality and authenticity studies based on the metabolic profiling of saffron have been well documented in the literature by using different analytical approaches. High‐performance liquid chromatography with diode array detector (HPLC‐DAD) was used to investigate isomers of both crocins and crocetin, safranal, picrocrocin, 4‐hydroxy‐2,6,6‐trimethyl‐1‐carboxaldehyde‐1‐cyclohexene (HTCC), and kaempferol content as well as to study the effect of drying methods on the metabolic content . Raman and FT‐IR were used to identify and quantify crocetin, dimethylcrocetin and crocins while gas chromatography with mass spectrometry (GC‐MS) was used to analyse aroma active compounds of saffron, such as isophorone, safranal, 4‐ketoisophorone, phenylethyl alcohol, 2‐pentanol, α , β ‐ionone, isophorone oxide .…”
Section: Introductionmentioning
confidence: 99%
“…High-performance liquid chromatography with diode array detector (HPLC-DAD) was used to investigate isomers of both crocins and crocetin, safranal, picrocrocin, 4-hydroxy-2,6,6-trimethyl-1-carboxaldehyde-1-cyclohexene (HTCC), and kaempferol content as well as to study the effect of drying methods on the metabolic content. [16][17][18][19] Raman and FT-IR were used to identify and quantify crocetin, dimethylcrocetin and crocins 13,20,21 while gas chromatography with mass spectrometry (GC-MS) was used to analyse aroma active compounds of saffron, such as isophorone, safranal, 4ketoisophorone, phenylethyl alcohol, 2-pentanol, α,β-ionone, isophorone oxide. [22][23][24][25] Moreover, the metabolic profile of saffron was investigated by NMR spectroscopy for quality and adulteration investigation.…”
mentioning
confidence: 99%